Comparison of a set of cognitive ability screening test for primary school-aged children in Indonesia (Medical Journal of Indonesia, 2020)
BACKGROUND Monitoring children’s intellectual development is important to align their educational needs. This study compared nonverbal intelligence subtest of the cognitive test battery for Individuals with or without intellectual disability (CIID) to measure visual logical reasoning, verbal intelligence subtest (verbal fluency [VF]–animal test) to assess vocabulary and semantic memory, and the modified Indonesian version of Hopkins verbal learning test (IHVLT) to assess learning ability and episodic memory, against the Wechsler intelligence scale for children (WISC) as an alternative cognitive screening tool in school-aged children. METHODS A cross-sectional study was conducted in 145 grade 1–6 elementary school students in Jakarta between March and May 2017. Performance on the CIID subtest, VF, and modified IHVLT was assessed by a pediatrician, and the WISC test was performed by a psychologist. The associations between variables were evaluated using nonparametric Spearman’s rank correlations, regressions, and box plots. RESULTS The correlation between total intelligence quotient (IQ) WISC and CIID was 0.42 (p<0.001) and 0.34 (p<0.001) for both IHVLT and VF. Box plots suggested possible discriminative capacity of CIID but insufficient specificity. However, CIID was associated with stunting (height) and health (weight) independent of age, sex, father’s education, or income. CONCLUSIONS The CIID subtest series, VF, and modified IHVLT correlated with total IQ WISC. However, CIID may be better to test predictors of poor cognitive performance in primary school-aged children than an IQ screening test.